Histopathological Characteristics of the Rat Thyroid Tissue After Cryotherapy - Pobelensky, Konstantin O.; Legach, Yevgeny I.; Pobelensky, Oleg N.; Pobelenska, Liliya A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 188.